Strengthening SME Financing Through the Holding Company Waqf Model: Governance Priorities from an ISM Approach in Indonesia - Vika Annisa Qurrata; Ermita Yusida; Vidya Purnamasari; Muhammad Hakimi Mohd Shafiai; Abdul Ghafar Ismail (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
This study addresses the limited attention given to governance mechanism required for implementing the Holding Company Waqf Model for SME financing in Indonesia. It is despite the growing discussion on cash waqf and alternative financing scheme. The study aims to identify and prioritize the governance factors required to support sustainable implementation of the model. Data were collected through in-depth interviews with seven experienced cash waqf managers in Malang during 2024. The ISM procedure involved the development of a Structural Self-Interaction Matrix (SSIM), reachability matrix, level partitioning, and driver-dependence analysis to determine the hierarchical relationships among governance variables. The findings reveal that regular and constant communication demonstrates the highest driving power (7) and functions as a key linkage variable in the governance hierarchy. Subjective norms and attitude toward behavior (driving power – 6 each) function as supporting independent variables. Meanwhile standard operating procedure and waqf legal protection as independent governance variables with strong driving influence. Also, the availability of regular monitoring and cash waqf blueprint model demonstrates high dependence on other governance elements. These results indicate that effective governance requires strong regulatory protection, operational clarity, and continuous supervision to reduce moral hazard and strengthen institutional trust. The novelty of this study lies in the integration of ISM into the governance analysis of the Holding Company Waqf Model, offering a structured governance hierarchy for SME financing implementation in Indonesia. The study also provides a practical governance framework that may support policymakers, waqf institutions, and SME stakeholders in developing sustainable financing mechanisms